Intramyocellular topography of lipid droplets and OXPAT in obesity and type II diabetes - Rui Fachada, Vasco (2010)
Nowadays in the westernized world, high caloric diet and sedentarism are driving populations to accumulate ectopic fat, especially in skeletal muscle. Such is associated with the development of insulin resistance (IR) related metabolic diseases, as type II diabetes (T2D) and obesity (OB). Like IR individuals, athletes also show high intramyocellular lipids (IMCL) contents, denoting qualitative rather than quantitative differences between insulin sensitive (IS) and IR individuals IMCL. PAT proteins and OXPAT specifically, are among the main regulators of lipid droplets (LDs) in skeletal muscle. We hypothesized that different IS profiles are distinguishable through LD and OXPAT localization and colocalization (COLOC) in different skeletal muscle fiber types. Biopsies from vastus lateralis were collected from 3 groups: lean controls (LC) (n=7), obese non diabetic (OB) (n=8) and type 2 diabetic (T2D) (n=10). Immunocytochemistry protocols and fluorescence microscopy were used, followed by bioinformatic methods. We assessed LD and OXPAT geography in relation to sarcolemma in different fiber types. Moreover, assessed data was also correlated with anthropometrical and blood variables. For group comparisons a Mann Whitney U test (P<0.001) was used and for variable correlations a Spearman test (P<0.05 and P<0.01) was used. LDs, OXPAT and COLOC showed more peripheral in T2D followed by OB when comparing to LC. OXPAT showed more peripheral than LDs in all fiber types of all groups, especially in type II fibers where OXPAT showed always more peripheral. LDs followed the same pattern with the exception of OB, where LDs showed more peripheral in type I than type II fibers. Moreover, such particle closeness to membrane correlated positively with tissue and plasma lipids, especially in T2D. When comparing to LC, the more peripheral values of LD and OXPAT in T2D and OB may be explained by tissue and plasma lipid availability. In type II fibers, more peripheral values may be explained by lesser capacity of these fibers in internalizing and metabolizing lipids. In OB type I fibers, more peripheral LDs may foresee an IR developing symptom. OXPAT more peripheral than LDs may be explained by OXPAT’s proposed role in packaging freshly internalizing lipids into new LDs for immediate oxidation. Our study brings novel insights concerning OXPAT localization in skeletal muscle. Additionally, we developed a powerful tool to study histological particle topography.